THERMAL MATURITY OF DEVONIAN ROCKS IN TERMS OF THEIR LITHOLOGICAL-FACIES AND AGE AFFILIATION. NORTHERN AND SOUTHERN SIDES OF THE DNIPRO-DONETS BASIN - KARPENKO, Ivan; CHUPRYNA, Anastasiia; KARPENKO, Oleksii (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. The production of hydrocarbons (HC) in open fields is decreasing, and the fields that were discovered in recent years, as a rule, are small in terms of reserves and can no longer provide a resource base for its expansion. An analysis of the experience of leading oil and gas companies shows that a significant expansion of the resource base and the discovery of significant reserves of hydrocarbon deposits can be obtained through the use of modern exploration technologies, which actively use in their arsenal the modeling of hydrocarbon systems in the studied territories. Carboniferous and Upper Devonian deposits remain the most promising stratigraphic complexes for the search for new deposits of explosives within the Eastern region of Ukraine. Methods. Mathematical statistics methods were used to create model constructions that allowed meaningful analysis of the original geological and geochemical information. The initial data were the results of laboratory studies by the pyrolysis method (Rock-Eval) of rock samples from search and exploration wells of the southern and northern sides of the Dnipro-Donets basin (DDB). In terms of lithology, the core samples were argillites (shales) – the vast majority, siltstones, sandstones, and limestones. Results. An important result of this study is that the feature of the spatial distribution of the main parameters of kerogen organic matter has been established, depending on the depth of the Devonian oil and gas source rocks, their age, as well as the location of the wells from which the core was taken, on the Northern or Southern sides of the DDB. Using the methods of mathematical statistics on the basis of cluster analysis, the classification of rock samples with a clay composition relative to the prevailing type of organic matter was performed based on the data of laboratory studies on the Rock-Eval apparatus. Conclusions. Quite high concentrations of organic matter in a significant number of studied samples (mainly in shales and limestones) were found at different depths, which are primarily corrected by the age of the Upper Devonian deposits. The regularities of changes in Tmax – the temperature of the maximum yield of hydrocarbons during kerogen cracking, depending on the depth of the location of rocks, which are distinct on the Southern and Northern sides of the DDB, have been established. This indicates different paleotectonic activity of the specified structural-tectonic elements in the post-Devonian period. On the South side, clay formations with a high kerogen content and high Tmax values are hypsometrically higher than on the Northern side of the Dnipro-Donets depression.